The Editorials: Towards Integrated Biodesign-related and Translational Plat-forms to Determine Co-Development for Adaptation of Innovative BIotechno ogies and to Prognosticate the Future of the Healthcare and Life Science Bio-industry - Medvedeva, Veronika; Moiseyakh, Marina; Grigorieva, Tatiana; Kobrinskii, Boris; Andronova, Natalia; Kovalev, Mikhail; Zemskov, Vladimir; Tyukavin, Aleksandr; Blokh, Sofia; Cheng, R. Holland; et al. (British Journal of Healthcare and Medical Research, 2022)
.